Bead Gel Preparation from Cassava Baggase Grafted Acrylamide and Carrageenan - Sperisa Distantina; Dea Espina Banowati; Laura Hanifa Aprian; Mujtahid Kaavessina (Program studi Teknik Kimia UNS, 2025)
Abstract. This research intends to prepare bed gels for medium of plant growth. Bead gels were prepared by grafting cassava bagasse by acrylamide with ammonium persulfate (APS) as the initiator using microwave energy. This research aims to examine the effect of the ratio of acrylamide to APS initiator on the swelling capacity. Briefly, cassava bagasse powder 1 g in 80 ml distilled water was mixed with acrylamide and APS to form grafted polimer by applying microwave. The resulted grafted polymer powder then was mixed with carrageenan to create bead gels. The formed bead gel was soaked in distilled water to test the swelling capacity. The highest swelling capacity in this research is 1183.333% at a ratio of 0.1 g APS : 15 g acrylamide and 1213.33% at a ratio of 10 g acrylamide : 0.1 g APS. Therefore, the swelling capacity increases with an increase in the ratio of acrylamide and APS. From the results of swelling capacity and FTIR, it can be concluded that the grafting process of cassava bagasse and acrylamide has been successfully conducted. Keywords:Ammonium persulfate, Bead gel, Grafting microwave, Swelling capacity, Cassava bagasse